Development and Characterization of Niosomal Formulations of Doxorubicin Aimed at Brain Targeting - Marco Bragagni; Natascia Mennini; Carla Ghelardini; Paola Mura (Frontiers Media S.A., 2012)
ABSTRACT - Purpose. The aim of the present work was the development and characterization of a niosomal formulation functionalized with the glucose-derivative N-palmitoylglucosamine (NPG) to obtain a potential brain targeted delivery system for the anticancer agent doxorubicin. Methods. Five different methods have been examined for vesicle preparation. Light scattering and transmission electron microscopy were used for vesicle characterization, in terms of mean size, homogeneity and Zeta potential, and selection of the best composition and preparation conditions for developing NPG-functionalized niosomes. Drug entrapment efficiency was determined after separation of loaded from unloaded drug by size exclusion chromatography or dialysis. Preliminary in vivo studies were performed on rats, injected i.v. with 12 mg/kg of doxorubicin as commercial solution (Ebewe, 2mg/mL) or NPG-niosomal formulation. Drug amounts in the blood and in the major organs of the animals, sacrificed 60 min post injection, were determined by HPLC. Results. The selected formulation consisted in Span:cholesterol:Solulan:NPG (50:40:10:10 mol ratio) vesicles obtained by thin-layer evaporation, leading to homogeneous vesicles of less than 200 nm diameter. This formulation was used for preparation of NPG-niosomes loaded with doxorubicin (mean size 161±4 nm, encapsulation efficacy 57.8±1.8%). No significant changes (P>0.05) in vesicle dimensions, Zeta potential or entrapment efficiency were observed after six months storage at room temperature, indicative of good stability. I.v. administration to rats of the NPG-niosomal formulation allowed for reducing drug accumulation in the heart and keeping it longer in the blood circulation with respect to the commercial formulation. Moreover, a doxorubicin brain concentration of 2.9±0.4 µg/g was achieved after 60 min, while the commercial solution yielded undetectable drug brain concentrations (